INFORMASI TEKNOLOGI DIDALAM MARKETING - Nanang Hoesen (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2011)
Currently,information and technology have been a part of our everday lives. Everything seems connected to each other via information and technology. Marketing is not an exception either. With today business competition increased to a very competitive level, marketing is one of the front liner that has big influence to a business survavibility. Many tools could help marketing to gain more market, and Information technology is one of the tools that could become a key to differentiated them to a whole new level,which in turn will attract new potential customer and even competitor’s customer. Marketingvia Information Technology mostly was done using two path. Thefirst was using more tradisional messaging system viasms mobile phone or email, and the other was using social media technology viainternet.The main objectiveofthis journal is tostudyandanalyze thebenefit of each the path taken, and also the the weakness of both. Do they must stand to each other or do they should collaborate to each other.